GuideAut: A Collaborative Platform Web to Support the Prototyping of Application Interfaces for Autistic People - Lopes, Diego; Valente, Danielle; Santos, Jonathas; Barreto, Raimundo; Rivero, Luis; Melo, Áurea (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC), 2025)
GuideAut is a collaborative web platform that supports the development of accessible interfaces for people with autism by organizing and validating inclusive design recommendations. Its main features include sharing and evaluating recommendations. The current version focuses on collaboration through sharing and validating content. An evaluation with 14 participants, based on the Technology Acceptance Model (TAM), showed positive results: 100% approval of the recommended features, 86.7% agreement that the design improved understanding, and 80% positive usability rating, indicating the potential of GuideAut as a collaborative accessibility tool.